Additional protocol to the UNASUR constitutive treaty on commitment to democracy - Suramericanas, Unión de Naciones (2013)
The Republic of Argentina, the Plurinational State of Bolivia, the Federative Republic of Brazil, the Republic of Chile, the Republic of Colombia, the Republic of Ecuador, the Cooperative Republic of Guyana, the Republic of Paraguay, the Republic of Peru, the Republic of Suriname, the Oriental Republic of Uruguay and the Bolivarian Republic of Venezuela, the Cooperative Republic of Guyana, subscribe in the city of Georgetown on the twenty-sixth day of the month of November of the year two thousand and ten,  in originals in the Spanish, English, Dutch languages and Portuguese, the four being equally identical.